ANALYSIS OF THE RELATIONSHIP BETWEEN PERSONAL SELLING, CUSTOMER SATISFACTION AND REPURCHASE INTENTION AMONG MOBILE VEGETABLE TRADER CUSTOMERS IN JEMBER - Ahmad Sauqi; Muhammad Firdaus; Karim Budiono; Farid Wahyudi (LPPM Institut Teknologi dan Sains Mandala, 2025)
The large number of highly educated male and female mobile vegetable traders in Jember is a phenomenon. Researchers are interested in examining the relationship between personal selling, customer satisfaction and customer repurchase intention among mobile vegetable traders. The population was customers of mobile vegetable traders in Jember, using a multistage sampling technique in 3 sub-districts, the sample was 30. Starting with the outer loadings test and ending with the direct and indirect influence test. Results. 1. Personal selling has a positive and significant effect on customer satisfaction. 2. Customer satisfaction has a positive and significant effect on repurchase intention 3. Personal selling has a positive and insignificant effect on repurchase intention, but will have a significant effect if customer satisfaction mediates personal selling with repurchase intention. Implications. 1. Mobile vegetable traders need to understand customer desires, be polite, build good relationships, promote honestly, be responsive and build communication. 2. Mobile vegetable traders need to create customer satisfaction in order to achieve repurchase intention. 3. To create satisfaction, excellent service, quality products and competitive prices are needed. The limitation of this research was that it was only carried out in 3 sub-districts. In future research, several sub-districts could be added. Keywords: Selling; Customers; Rephurchase; Mobile; Vegetable